2020
DOI: 10.2147/ott.s259016
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resveratrol Suppresses Tumor Progression via Inhibiting STAT3/HIF-1α/VEGF Pathway in an Orthotopic Rat Model of Non-Small-Cell Lung Cancer (NSCLC)</p>

Abstract: Background: The STAT3/HIF-1α/VEGF pathway is associated with the development and progress of various tumors including NSCLC. The aim of the present study was to investigate whether resveratrol (RES) could suppress NSCLC progression via inhibiting the expressions of STAT3, HIF-1α, and VEGF in a nude rat model. Methods: Twenty-four nude rats were randomly divided into control, NSCLC, and NSCLC+RES groups. An orthotopic rat model of NSCLC was established. The animals in the NSCLC+RES group received the same opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…It would be more meaningful should the anti-ATC efficacy can be proved in vivo. A body of evidence reveals the anticancer effects of resveratrol on a wide range of human malignancies in vitro [15,[50][51][52][53]. However, the corresponding in vivo data remain limited because trans-resveratrol can be efficiently metabolized to the less effective cis-resveratrol [54] and quickly eliminated from the body when it is administered systemically [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…It would be more meaningful should the anti-ATC efficacy can be proved in vivo. A body of evidence reveals the anticancer effects of resveratrol on a wide range of human malignancies in vitro [15,[50][51][52][53]. However, the corresponding in vivo data remain limited because trans-resveratrol can be efficiently metabolized to the less effective cis-resveratrol [54] and quickly eliminated from the body when it is administered systemically [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is constitutively activated in many tumor types. Studies have shown that RSV effectively prevents cancer by inhibiting STAT3 expression (51). It also has an inhibitory effect on antiapoptotic mediators such as NF-kB, COX-2, phosphatidylinositol 3-kinase (PI3K), and mTOR (52).…”
Section: Modulates Inflammation-related Cancermentioning
confidence: 99%
“…STAT3 is downregulated by resveratrol administration concomitantly with an attenuation of HIF-1α as well as VEGF levels in xenograft models of lung cancer [ 96 ], indicating the inhibitory function of resveratrol in hypoxia-mediated angiogenesis. In gastric cancer, resveratrol suppresses the HIF-1α/Hh signaling axis, reversing hypoxia-driven cell invasion and the EMT process [ 97 ].…”
Section: Natural Polyphenolic Compoundsmentioning
confidence: 99%